Obligation to Negotiate Access to the Pacific Ocean (Bolivia v. Chile) - Dunkelberg, Alonso Gurmendi (The American journal of international law, 2019)
More than thirteen decades after Chile annexed Bolivia's coastal regions, the International Court of Justice (ICJ) denied Bolivia's longstanding claim that Chile had undertaken a legal obligation to negotiate granting it sovereign access to the Pacific Ocean.